PEMBERDAYAAN KELOMPOK WANITA TANI MIGUNANI NANGGULAN KULON PROGO MELALUI PENGEMBANGAN TANAMAN JAGUNG - Stefani, Eska; Sudrajat, Ignasius Suprih; Darini, Maria Theresia; Setiawati, Evi (Jurnal Abdimas Bina Bangsa, 2024)
Kulon Progo Regency still depends on Magelang and Klaten to meet its functional food needs for sweet corn cobs. The Migunani Women's Farmers Group (KWT) has high potential for developing food crops. With the large area of land owned and the Angora group which is still relatively young. The method used in this service is socialization and mentoring. The result of this service is an empowerment program through the development of sweet corn plants in the Migunani Women's Farmers Group (KWT), Nanggulan, Kulon Progro which has succeeded in increasing corn production. With the support of socialization and mentoring, it is hoped that this program can continue and become a model of empowerment for other farmer groups in the Kulon Progo region.